What Radiology Residents Need to Know: Musculoskeletal Radiology - Eisenberg, Ronald L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is an introduction to musculoskeletal radiology, specifically designed for the needs of first-year residents. On the first rotation in musculoskeletal imaging, radiology residents are asked to learn significant amounts of information at a fast and unrelenting pace. However, most current books are densely written and contain far more material than residents need to know. Moreover, the number, variety and quality of images is often limited. What Radiology Residents Need to Know: Musculoskeletal Radiology answers these needs by presenting the important information in bullet fashion, divided into convenient sub-units, such as (3z(Bclinical information,(3y z(Bimaging findings,(3y (Band (3z(Bmanagement.(3y (BIn most cases, an individual pathological condition can be presented in one page or less. In addition, it contains tips on approaching and interpreting radiographs, MRI and CT based on decades of practical experience and teaching residents at the work station. With liberal use of illustrations in the text and an online bank of many more high-quality images, this book gives readers a comprehensive library of musculoskeletal imaging scans and serves as an ideal guide for radiology residents.s
Trauma: Introduction and Spine -- Trauma: Upper Extremity -- Trauma: Pelvis, Hip, Lower Extremity and Avulsion Injuries -- Periosteal Reaction -- Benign Bone Tumors and Tumor-Like Conditions -- Malignant Bone Tumors -- Soft-Tissue Lesions -- Arthritis -- Metabolic, Endocrine, and Hematologic/Bone Marrow -- Avascular Necrosis (AVN) -- Infections -- Normal Variants and "Don't Touch" Lesions -- Miscellaneous Conditions (By Skeletal Area) -- Miscellaneous Lesions (No Specific Skeletal Area) -- Surgical Interventions. .
Keywords: Radiology; Orthopedics; Radiology; Orthopaedics; Musculoskeletal System -- diagnostic imaging; Musculoskeletal Diseases -- diagnostic imaging; Wounds and Injuries -- diagnostic imaging; Handbook